> eqns := {(x[1]+1)^2+y[1]^2 = (x[2]-1)^2+y[2]^2, (x[1]-c[1])^2+(y[1]-c[2])^2 = (x[3]-1)^2+y[3]^2, (x[2]-c[1])^2+(y[2]-c[2])^2 = (x[3]+1)^2+y[3]^2, y[1](x[3]+1) = y[3](x[1]+1), y[2](x[3]-1) = y[3](x[2]-1), (x[2]-c[1])(y[1]-c[2]) = (x[1]-c[1])(y[2]-c[2])};

print(`output redirected...`); # input placeholder

/ 2 2 2 2

{ (x[1] + 1) + y[1] = (x[2] - 1) + y[2] ,

\

2 2 2 2

(x[1] - c[1]) + (y[1] - c[2]) = (x[3] - 1) + y[3] ,

2 2 2 2

(x[2] - c[1]) + (y[2] - c[2]) = (x[3] + 1) + y[3] , x[2](y[1

] - c[2]) - c[1](y[1] - c[2]) = x[1](y[2] - c[2])

- c[1](y[2] - c[2]), y[1](x[3] + 1) = y[3](x[1] + 1),

\

y[2](x[3] - 1) = y[3](x[2] - 1) }

/

> vars := {x[1], x[2], x[3], y[1], y[2], y[3]};

print(`output redirected...`); # input placeholder

{x[1], x[2], x[3], y[1], y[2], y[3]}

> solve(eqns, vars);

%;

Warning, solutions may have been lost

How to solve this equations? Thank you!

Best reguard

luoqi67@163.com